(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Caffeine was investigated for its possible fetal programming effects on reproductive function of male offspring. Sixty-five pregnant Wistar rats were grouped into four. Group 1 was control and received distilled water. Groups 2, 3 and 4 were treated orally with 1.14, 3.42 and 5.70 mg/kg body weight of caffeine respectively. Each group was subdivided into four based on gestation days (GD) 1-7, 8-14, 15-21 and 1-21. The day of parturition was taken as postnatal day zero (0). Male offspring were sacrificed on postnatal day 70. Parameters determined were: weight at birth, body weight at postnatal day 21 and 70, anogenital distance (AGD) index, sperm parameters, reproductive organ weight, histology and hormonal profile (testosterone, FSH and LH). Data were analyzed using Analysis of Variance. Level of significance was taken at P<0.05. Male offspring belonging to caffeine treated dams showed dose dependent significant decreases in birth weight. Male offspring from dams treated with caffeine during GD 1-7 and GD 1-21 had a significant increase in their AGD index. Also, male offspring from dams treated with 1.14 and 5.70 mg/kg body weight of caffeine during GD 8-14 had a significant increase in AGD index. Dams treated with 3.42 mg/kg body weight of caffeine during GD 15-21, had a significant increase in the AGD index of their male offspring. The sperm motility of offspring from dams treated with 5.70 mg/kg body weight of caffeine during GD 1-7 and GD 1-21 were significantly increased. Offspring of GD 8-14 and GD 15-21 dams treated with 3.42 and 5.70 mg/kg body weight of caffeine respectively, showed significantly reduced serum testosterone level. There was a significant decrease in the weight of testes of offspring from dams treated with caffeine during GD 8-14. Histological sections of testes of offspring from caffeine treated dams showed interstitial congestions, edema, reduced germinal epithelial height and detached basal membrane. Maternal caffeine exposure during different gestational periods adversely affected birth weight and some reproductive indices in male offspring of Wistar rats.